[PP.29.19] VISFATIN SERUM LEVEL AND EXPRESSION IN SUBCUTANEOUS AND VISCERAL ADIPOSE TISSUE IN PREPUBERTERTAL BOYS: RELATION TO BLOOD PRESSURE AND METABOLIC PARAMETARS. (September 2016) - Relatic, K. Selthofer; Novak, S.; Divkovic, D.; Drenjancevic, I.; Cosic, A.
Abstract : Objective: Childhood obesity presents a risk factor for adult atherosclerosis, hypertension and cardiometabolic diseases. Visfatin, an adipocytokine with inflammatory/enzymatic properties, is involved in atherogenesis and adipose tissue angiogenesis. Predominantly produced in visceral adipose tissue (VAT), less in subcoutaneous adipose tissue (SAT), muscles, liver, cardiac cells, peripheral blood neutrophils. In adolescents and adults is a part of metabolic syndrome and could present a marker of visceral adiposity. The aims of study were to determine the physiological values of serum visfatin concentrations, visfatin mRNA expression in SAT and VAT in childhood and its relation to anthropometric/metabolic/blood pressure (BP) level. Design and method: The study included 59 healthy boys, hospitalized for elective surgery, divided according to age into group I (1–3 years old), group II (3–7 years old) and group III (7–10 years old). Anthropometric, biochemical and BP measurements were done to all patients. The total visfatin serum were determined by ELISA immunoassay test, and mRNA level in SAT and VAT by real-time PCR. Results: Body weight and height were significantly different in all age groups, where body mass index was statistically higher in the third age group (p = 0.011). All groups statistically differ from each other in waist circumference (p < 0.001), but without difference in waist-to-hip ratio (p = 0.099). Group III had statistically higher systolic BP compared with groups I and II (p = 0.003), but the diastolic BP was statistically higher only in group III compared with group I (p = 0.009), all in the normal range values. Fasting morning glucose level, CRP, triglycerides, cholesterol, LDL and HDL levels did not significantly differ between groups, also as serum visfatin concentrations. Visfatin mRNA expression was higher in SAT compared with VAT in all three groups. Conclusions: The included subjects were metabolically healthy with normal glucose level, lipidogram and systolic/diastolic BP. Lack of correlation of visfatin serum level and mRNA expression in SAT and VAT with BP and metabolic parametars can be explained by the underdeveloped inflammation of adipose tissue, indicating that the maturation physiology and ageing process have an important part in the development of pathophysiological processes.